2007
DOI: 10.1590/s0004-27492007000100017
|View full text |Cite
|
Sign up to set email alerts
|

Flicker perimetry in healthy subjects: influence of age and gender, learning effect and short-term fluctuation

Abstract: This study suggests that, in healthy subjects, critical fusion frequency decreases with age, that flicker perimetry is associated with a learning effect, and that a moderately high short-term fluctuation is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…Several studies showed that healthy and glaucomatous individuals can exhibit a learning effect with repeated standard automated perimetry testing (8)(9)(10)(11)(12)(13)(14)(15)(16) . This effect was also demonstrated in short wavelength automated perimetry (17)(18) , flicker perimetry (19) , and frequency doubling perimetry (20)(21)(22)(23)(24)(25) .…”
Section: Introductionmentioning
confidence: 66%
“…Several studies showed that healthy and glaucomatous individuals can exhibit a learning effect with repeated standard automated perimetry testing (8)(9)(10)(11)(12)(13)(14)(15)(16) . This effect was also demonstrated in short wavelength automated perimetry (17)(18) , flicker perimetry (19) , and frequency doubling perimetry (20)(21)(22)(23)(24)(25) .…”
Section: Introductionmentioning
confidence: 66%
“…35 Several (flicker) perimetry studies show systematical variation between measurements and it is suggested that these are learning and fatigue effects. [36][37][38][39] However, for single frequency temporal contrast measurements, it is mentioned that fatigue effects are small, due to the relative simplicity and short duration (a few minutes) of the measurement. 12 In addition, the 2AFC method applied in this study shows no learning effects, i.e., there is no systematical difference between subsequent measurements, as can be seen in Fig.…”
Section: Journal Of Biomedical Opticsmentioning
confidence: 99%
“…13 The learning effect for SAP was extensively studied showing an increase in the absolute mean sensitivity with subsequent examinations. [14][15][16] This effect was also shown in short wavelength automated perimetry, 17,18 flicker perimetry, 19 and frequency doubling perimetry. [20][21][22][23] The aim of this study was to evaluate the learning effect across multiple tests in HMP using the full-threshold 24-2 strategy in healthy patients without perimetric experience.…”
Section: Introductionmentioning
confidence: 59%